Implementasi Disiplin Aparatur Desa di Desa Gantar Kecamatan Gantar Kabupaten Indramayu - Patkur Rohman; Abdur Rahim (STAATSRECHT: Indonesian Constitutional Law Journal, 2020)
AbstractThe performance of village office staffs that still has many weakness related to the recruitment which was based on the family relation and not based on professionalism and also there were many public service that did not run well and smoothly. Islam rules this life based on Al-Qur’an and Hadith and it has good management in regulating the government by prioritizing the education of aqidah Islamiyah as the base of organizing the country and nurturing the noble attitude and behavior. The researcher was interested and encouraged to study and investigate the discipline of village office staffs especially at Gantar Village The aims of this research are to find out how is the discipline of village officestaffs in running their daily duties and how is the discipline implementation of village office staffs according to The Law Number 6 in 2014. This research employed analytical descriptive research by describing the discipline practice applied by the village chief of Gantar as the person in charge of the village government. The results of this research, it is found out that the work discipline expected by the government through The Law Number 6 in 2014 for each staff of village office at Gantar Village is less maximal. This was proven by the village office staff who did not obey the work hours either when it supposed to be started or when it supposed to go home, even the performance is still very poor. The control of the village chief as the executif officer at the village is not maximal yet. There are still some village office staffs that are not active for three months but still free of any reprimand letter, sanction until firing based on the suggestion from BPD (The Board of Village Representative) and The Law Number 6 in 2014. This condition is complained by most of the villagers because they need good public service. Keywords: Discipline, Village office Staffs, Islamic Law, The Law Number 6 in 2014AbstrakKinerja Aparatur ditingkat desa masih banyak terdapat kekurangan terkait dengan rekrutment yang didasari dengan orang-orang dekat bukan karena profesionalitas, dan masih banyaknya pelayanan publik yang seharusnya dilayani oleh aparatur desa belum berjalan dengan lancar. Islam mengatur tata kehidupan dengan landasan al-Quran dan Hadist, Islam mempunyai manjemen yang baik dalam mengatur pemerintahan dengan mengedepankan pendidikan aqidah Islamiyah sebagai dasar bernegara, pembinaan ahlaq dan penjelasan secara teratur. Penulis tertarik dan terdorong untuk mengkaji dan meneliti tentang Implementasi  Disiplin Aparatur Desa, khususnya yang berada di Desa Gantar, bagaimana disiplin aparatur desa dalam mejalankan tugas setiap harinya. Bagaimana  implementasi disiplin aparatur desa menurut UU No.6 Tahun 2014.  Penelitian ini mengunakan metode deskriptif analitik dengan cara menggambarkan praktek disiplin yang diterapkan oleh kepala Desa Gantar selaku penanggungjawab Pemerinatahan desa. Hasil penelitian ini diketahui bahwa disiplin kerja yang telah dicanangkan oleh pemerintah melalui UU No. 6 Tahun 2014 bagi setiap aparatur desa gantar kurang maksimal hasilnya. Hal ini terbukti masih adanya Aparat Desa yang tidak mengindahkan jam kerja baik sewaktu mulai kerja maupun jam pulang, bahkan kinerjanya masih tumpang tindih.  Kontrol kepala desa sebagai Pejabat eksekutif di desa belum maksimal. Masih terdapat beberapa aparat desa yang tidak aktif selama 3 bulan tapi belum mendapatkan surat teguran, sanksi hingga pemecatan sesuai dengan saran dari BPD (Badan Pengawas Desa) dan UU No.6 Tahun 2014. Kondisi ini dikeluhkan oleh sebagian warga yang perlu pelayanan publik.Kata kunci: Disiplin, Aparatur desa, Hukum Islam, UU No. 6 Tahun 2014